Daslne: the challenge of developing a regional database for autism spectrum disorder. Issue 1 (2nd May 2008) - McConachie, H; Barry, R; Spencer, A; Parker, L; Le Couteur, A; Colver, A
Abstract : The setting up of a database of children with autism spectrum disorder (ASD) in the north east of England is described. Best practice has been followed and included involving parents in planning and implementation at all stages, oversight by a multi-agency group, management by a multidisciplinary steering group, and independent administration of the database. From a potential listing of 986 children with ASD aged 3–12 years, the parents of 511 have so far responded (51.8%), although response rate varies considerably by local authority. Data checking has shown the information to be valid and case ascertainment broadly representative. The uses to which the data are being put and the continuing challenges are outlined.